A national eHealth vision developed by University Medical Centres: A concept mapping study. (January 2020) - Rauwerdink, Anneloek; Kasteleyn, Marise J.; Haafkens, Joke A.; Chavannes, Niels H.; Schijven, Marlies P.; ,; ,
Highlights: eHealth should contribute significantly to 'patient participation and empowerment'. A concept mapping approach is highly eligible in reaching consensus. Five themes concerning eHealth to focus on for the next few years were identified. Abstract: Background: EHealth solutions are envisaged to contribute significantly to a sustainable healthcare system. Between 2016 and 2018 the eight Dutch University Medical Centers (UMCs) received Dutch Government's funding to undertake research into the clinical impact, cost-effectiveness and ethical consideration of eHealth. The UMCs collaborated within the consortium 'Citrien fund (CF) program eHealth' and found that, in order to increase the value of eHealth in routine care, a national vision on eHealth developed by the UMCs was warranted. Objective: The objective of this paper was to elucidate the process of the 'Netherlands Federation of UMCs (NFU) eHealth vision' development by describing the results of the performed concept mapping study. Methods: A concept mapping approach was followed. Sixteen members of the steering committee of the CF program eHealth were selected as participants. First, each member selected relevant objectives from the eight individual UMC eHealth vision documents, which was to be incorporated into the overall 'NFU eHealth vision'. Second, objectives were rated for necessary to be included in the vision document and the need to achieve the objective within five years. Thereafter, the objectives were sorted into self-created thematic clusters. And finally, the concept map with the thematic clusters and corresponding objectives was discussed with the steering committee to determine the major themes of the 'NFU eHealth vision'. Results: 38 objectives were determined by the steering committee and grouped into the following 6 thematic clusters on the concept map: 'patient participation and empowerment'; 'infrastructure'; 'education and research'; 'multi-disciplinary care'; 'organisational restructuring'; and 'essential conditions for development of eHealth solutions'. After discussing the concept mapping results with the steering committee, the following five major themes were determined to be addressed in the vision document: 'patient and caregiver'; 'research and innovation'; 'education'; 'organisation of care'; and 'essential conditions for development of eHealth solutions'. Conclusion: Concept mapping was successfully applied to conceptualise the different values and opinions of the eight Dutch UMCs in order to develop a national vision on eHealth. This vision document will give direction to the development, evaluation and implementation of eHealth in the eight Dutch UMCs and their adherent healthcare providers.